VISUAL IMAGES AS A TOOL OF VOCABULARY TEACHING - Korol , Larysa (Collection of scientific papers «ΛΌГOΣ», 2022)
Visualization is very important for language teaching in general and for EFL learners in particular as an effective tool in vocabulary activities. Harmer states the status of vocabulary by saying: “If language structure makes up the skeleton of language, then it is the vocabulary that provides the vital organs and the flesh.”